RESERVES OF RAW MATERIALS OF HARMALA VULGARIS (PEGANUM HARMALA L.) IN CERTAIN TERRITORIES OF BATKEN AND OSH REGIONS OF THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article provides information about the distribution areas and natural reservesof raw materials of harmala vulgaris (Peganum harmala L.) in certain areas of Batken and Oshregions. We have noted natural thickets of harmala vulgaris on ten different plant communities ona total area of 92.8 hectares. The operational reserve is 40.37 tons, the volume of possible annualharvesting, taking into account the resumption, was 10.09 tons.
Keywords: formation, floristic composition, association, projective cover, productivity, operational reserve.